2014
DOI: 10.1080/10810730.2013.821557
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Information Needs of Lower Income Cancer Survivors: Results of a Randomized Control Trial Evaluating the American Cancer Society's “I Can Cope”

Abstract: The American Cancer Society is a leader in the development of cancer survivorship resources. One resource of the American Cancer Society is the I Can Cope program, an educational program for cancer survivors and their families. Evaluations of this program indicate that cancer patients highly rate its objectives. Yet, there are gaps in the understanding of the full impact of the program on diverse cancer survivors. In this study, the authors used a randomized trial to evaluate the program. Participants included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…That is, some cancer survivors may perceive their limitations as more significant than they are in reality, while others may think they can work harder than they actually can. Previous research implies that more information regarding illness implications (eg, treatment side effects) is needed for cancer survivors with lower health literacy (ie, the capacity to obtain, process, and understand health information), eg, and lower education level …”
Section: Discussionmentioning
confidence: 99%
“…That is, some cancer survivors may perceive their limitations as more significant than they are in reality, while others may think they can work harder than they actually can. Previous research implies that more information regarding illness implications (eg, treatment side effects) is needed for cancer survivors with lower health literacy (ie, the capacity to obtain, process, and understand health information), eg, and lower education level …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that ALEX1 overexpression induced cell apoptosis in SK-BR3 breast cancer cells by Hoechst staining and flow cytometric analysis, conversely, ALEX1 depletion inhibited MCF-7 breast cancer cells apoptosis (Figure 6, 7). One of the important apoptotic pathways is mitochondrial-mediated signal pathway (Martin et al, 2014). Mitochondria participate in the so-called intrinsic pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Six interventions/publications reported results on pain management (intensity, severity, and perception) during treatment or follow‐up . All aimed to reduce inequalities based on ethnicity/race or socioeconomic level and mostly targeted women with breast cancer.…”
Section: Resultsmentioning
confidence: 99%